Activity of Serbian Aronia prunifolia against Prototheca wickerhamii and Prototheca zopfii - Suvajdžić, Ljiljana; Krstić, Tamara; Stojanović, Srđan; Grujić-Letić, Nevena; Milankov, Olgica; Gigov, Slobodan; Petrović, Nemanja; Svirčev, Zorica; Ilić, Nebojša (Acta Scientiae Veterinariae, 2017)
Background: Beneficial effects of berries have been known from 16th century, but their antimicrobial effects have been explained scientifically only recently. The two most common aronia species are black chokeberry, Aronia melanocarpa [Michx.] Elliot and red chokeberry, Aronia arbutifolia [L.] Elliot. Purple chokeberry (Aronia prunifolia) is a hybrid of these two species. Protothecosis is a disease caused by achlorophyllous algae Prototheca species. Infections with Prototheca species are more common in veterinary medicine. The purpose of this study was to investigate the activity of Aronia prunifolia berries against Prototheca zopfii (P. zopfii) and Prototheca wickerhamii (P. wickerhamii). Materials, Methods & Results: Purple chokeberry juice was made by squeezing the fruits and evaporated to dryness. Extracts of purple aronia were obtained by maceration with ethanol 80 % (v/v) for 24 h. Prototheca zopfii was obtained from udder of cow with mastitis and Prototheca wickerhamii was isolated from human oral cavity. Total phenolic and flavonoid contents were analized using spectrophotometric methods. The chemical composition of the tested substances was determined by a high performance liquid chromatography (HPLC) method. The examination was conducted by a micro-dilution method according to the guidelines of Clinical and Laboratory Standards Institute (CLSI). Microsoft Excel program 2007 was used for statistical analysis. The antialgal activity was expressed as minimal inhibitory concentrations MIC99, MIC90 and MIC80, the lowest concentration which kills 99%, 90% and 80% of organisms, respectively. Furthermore, minimal algaecide concentration (MAC), the lowest concentration which kills 99.9% of organisms is determined, as well as break point, the lowest concentration at which there is no algal growth. Discussion: The content of ascorbic acid was twice as high in the ethanolic extract as in the juice. Content of polyphenolic compounds was high in both juice and ethanolic extract. The quantity of phenocarbonic acids in juice and ethanolic extract was relatively low. Some of them were found only in juice (ellagic, coumaric and gentisic acids) as opposed to others found only in ethanolic extract (chlorogenic acid). Flavonoids were also detected in juice and ethanolic extract. Extract was much richer in flavonoid content when compared to aronia juice. Catechin was present in concentration of 186.3 mg/ 100 g of dry matter in the aronia juice, and 680.65 mg/ 100 g of dry matter in the ethanolic extract, which was more than 3.6 times higher. Quercetin was found only in the extract. The rutin content was 12 times and the chrysin content was 2.5 times higher in the aronia extract. The biggest difference could be noted in the quantitative contents of anthocyanins, 26 times higher concentration in extract than in juice. In general, higher content of bioactive compounds could be observed in the extract than in the juice. The results showed that the ethanolic extract of aronia fruits exhibited antialgal activity against both Prototheca species, while the juice showed no antialgal activity. This difference in antialgal effect is presumably related to the high content of several groups of biocompounds, especially catechin and anthocyanins, present in the ethanolic extract, and probably their synergistic action. There is no comparable data of antialgal effects of aronia in literature.